Private and public bank consumers’ preference in Kathmandu Valley: Evidence from customers’ satisfaction index - Udbodh Bhandari; Sanjeet Yadav; Niranjan Devkota; Udaya Raj Paudel; Sharad Rajbhandari; Dipendra Karki (International Research Journal of Science, Technology, Education, and Management, 2021)
Free and open market competition has enhanced both public and private sectors to compete with each other. Rather than sentimental, these days’ sectors are getting popularity as per their performance and customers’ satisfaction. Although banks are divided into private and public as per their establishment, both are targeting the public. Customers’ preferences derived their success. This paper aims to identify customers’ preferences among public and private banks in Kathmandu valley. To identify their preferences, 302 respondents, mainly adults aged 20-40, from the Kathmandu valley are selected as a sample. The study is based on a descriptive cross-designed where Customers’ Satisfaction Index has been developed to classify their preference of private and public banks. SERVQUAL model has been adopted to see the factors affecting customers’ preference of private and public banks. This study finds that 86.4% of customers compare between the banks, and 85% consider primarily interest rate while deciding to open a bank account. The result from the overall satisfaction index indicates that those customers having an account in private banks are more satisfied than the public bank customers in various dimensions. Customers using both the banks are facing several problems mainly from employees and managers time and again, but such problems are more with public banks customers compared to private banks customers. Interestingly, 91.75% (95.25% from public banks and 90.79% from private banks) respondents mentioned that those challenges that customers were facing in the bank are solvable. Embracing new technologies, personalizing the customer experience, employee motivation and relationship-based pricing are the main strategies that both – private and public banks can adopt to satisfy their customers.